2008
DOI: 10.1158/1078-0432.ccr-08-1014
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Gefitinib, 5-Fluorouracil, Leucovorin, and Oxaliplatin in Previously Untreated Patients with Metastatic Colorectal Cancer

Abstract: Purpose: We investigated the gefitinib, 5-fluorouracil (5-FU), leucovorin and oxaliplatin (IFOX) regimen as first-line therapy in patients with metastatic colorectal cancer. Experimental Design: Eligible patients had stage IV colorectal adenocarcinoma, and had not received prior chemotherapy for metastatic disease. Each cycle consisted of 14 days. Cycle 1 consisted of oxaliplatin, leucovorin, and 5-FU (FOLFOX-4). All subsequent cycles consisted of FOLFOX-4 with gefitinib at 500 mg orally daily throughout th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…First-line treatment included a backbone of an irinotecan-fluoropyrimidin or oxaliplatin-fluoropyrimidin-based CTX with the addition of a VEGF (bevacizumab), EGFR (cetuximab, panitumumab), or RTK (sunitinib, sorafenib, imatinib, gefitinib) inhibitor when appropriate, as described before (Awada et al 2011;Blesa and Pulido 2010;Cutsem et al 2007;Fisher et al 2008;Hurwitz et al 2004;Kelley et al 2013;Kindler et al 2005;Peeters et al 2010;Qvortrup et al 2010;Samalin et al 2014;Tournigand et al 2004). As a second-line treatment backbone CTX was continued in a crossover design, while VEGF, EGFR, or RTK inhibition was either discontinued or switched over (see Fig.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…First-line treatment included a backbone of an irinotecan-fluoropyrimidin or oxaliplatin-fluoropyrimidin-based CTX with the addition of a VEGF (bevacizumab), EGFR (cetuximab, panitumumab), or RTK (sunitinib, sorafenib, imatinib, gefitinib) inhibitor when appropriate, as described before (Awada et al 2011;Blesa and Pulido 2010;Cutsem et al 2007;Fisher et al 2008;Hurwitz et al 2004;Kelley et al 2013;Kindler et al 2005;Peeters et al 2010;Qvortrup et al 2010;Samalin et al 2014;Tournigand et al 2004). As a second-line treatment backbone CTX was continued in a crossover design, while VEGF, EGFR, or RTK inhibition was either discontinued or switched over (see Fig.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…[20][21][22][23][24] The studies reviewed reported grade 3 nausea or vomiting in 18% to 27% of patients. 13,16 Prophylactic antiemetic therapy with a steroid and serotonin antagonist is recommended. [21][22][23][24] One group suggests that addition of a neurokinin (NK 1 ) antagonist may be appropriate in some patients.…”
Section: Supportive Carementioning
confidence: 99%
“…Serum bilirubin (1) Less than or equal to 1.5 mg/dL. 13 (2) Less than or equal to 1.5 times ULN. 16 b. ALT/ AST less than or equal to 2.5 times the ULN 13,16 or less than or equal to 5 times the ULN if liver metastases were present.…”
Section: Hepatic Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several phase II studies found little additional benefit of EGFR TKI on a conventional chemotherapy platform (Hofheinz et al, 2006;Chau et al, 2007;Gelibter et al, Zampino et al, 2007;Cascinu et al, 2008;Fisher et al, 2008;Stebbing et al, 2008). More importantly, excessive toxicities were encountered in a number of these studies, especially with irinotecan combinations.…”
Section: Epidermal Growth Factor Receptormentioning
confidence: 99%